ABA and GA3 regulate the synthesis of primary and secondary metabolites related to alleviation from biotic and abiotic stresses in grapevine - Murcia, Mauro German; Fontana, Ariel; Pontin, Mariela Ana; Baraldi, Rita; Bertazza, Gianpaolo; Piccoli, Patricia Noemí (2018)
Plants are able to synthesize a large number of organic compounds. Among them, primary metabolites are known to participate in plant growth and development, whereas secondary metabolites are mostly involved in defense and other facultative processes. In grapevine, one of the major fruit crops in the world, secondary metabolites, mainly polyphenols, are of great interest for the wine industry. Even though there is an extensive literature on the content and profile of those compounds in berries, scarce or no information is available regarding polyphenols in other organs. In addition, little is known about the effect of plant growth regulators (PGRs), ABA and GA3 (extensively used in table grapes) on the synthesis of primary and secondary metabolites in wine grapes. In table grapes, cultural practices include the use of GA3 sprays shortly before veraison, to increase berry and bunch size, and sugar content in fruits. Meanwhile, ABA applications to the berries on pre-veraison improve the skin coloring and sugar accumulation, anticipating the onset of veraison. Accordingly, the aim of this study was to assess and characterize primary and secondary metabolites in leaves, berries and roots of grapevine plants cv. Malbec at veraison, and changes in compositions after ABA and GA3 aerial sprayings. Metabolic profiling was conducted using GC-MS, GC-FID and HPLC-MWD. A large set of metabolites was identified: sugars, alditols, organic acids, amino acids, polyphenols (flavonoids and non-flavonoids) and terpenes (mono-, sesqui-, di- and triterpenes). The obtained results showed that ABA applications elicited synthesis of mono- and sesquiterpenes in all assessed tissues, as well as L-proline, acidic amino acids and anthocyanins in leaves. Additionally, applications with GA3 elicited synthesis of L-proline in berries, and mono- and sesquiterpenes in all the tissues. However, treatment with GA3 seemed to block polyphenol synthesis, mainly in berries. In conclusion, ABA and GA3 applications to grapevine plants cv. Malbec influenced the synthesis of primary and secondary metabolites known to be essential for coping with biotic and abiotic stresses.